Is an inefficient transmission market better than none at all? On zonal and nodal pricing in electricity systems - Joachim Bertsch (Institute of Energy Economics at the University of Cologne (EWI), 2015)
In this paper, the trade-off between inefficient transmission forward markets (in nodal pricing regimes) and the inefficiency induced by hiding transmission constraints from the market (in zonal pricing regimes) is analyzed. First, a simple two node model formalizing the general trade-off is developed.Then, comparative statics are performed with a stochastic equilibrium model including more nodes, loop flows and an energy and transmission forward market. Inefficiency in the transmission forward market is introduced via a bid-ask-spread and risk aversion of market participants. The welfare impacts for abroad range of supply, demand, grid and inefficiency parameters are analyzed numerically. For efficient spot and forward markets, the results of the literature of nodal pricing being the efficient benchmark are confirmed. With inefficient transmission forward markets, however, zonal pricing proves advantageous in situations with little congestion and low costs. The results imply that the trade-off between the pricing regimes should be considered carefully when defining the geographical scope of bidding zones.
Keywords: D47; Q40; L10; 330; Electricity; Market Design; Transmission Forward Markets; Inefficient Markets